The Edu-Act Collaboration Of Holistic Green Business - Anggreniko, Litya Surisdani; Chandra Sari, Kartika Dwi; Velinia, Santi; Kuncoro, Puguh Dwi (Universitas Negeri Semarang, 2025)
Increasing awareness of cosmetic use increases the quantity of consumption carried out by customers, which poses a real threat related to the increase in cosmetic waste produced. In 2022, there is data on the largest cosmetic purchases in Indonesia, which has been dominated by PT. Paragon Innovation Technology (PT. PTI). The purpose of this service activity is to make all actors responsible for the sustainable use of cosmetics, not only from the producer side but also from the consumer. All community service methods are carried out in various series of activities this time, namely online and offline FGDs, games, simulations and seminars to several communities that are felt to be able to support the company's green business movement. In answering the needs of partners, the team stringed together 8 diverse activities together with collaborators involved in these activities. In the entire series of activities, the team emphasizes the formation of a green behavior mindset in daily life, including the use of cosmetics to personal waste management. Community service is expected to have an impact on paragonians to be able to be responsible for consumption patterns by introducing various options that are easy to apply in the future.